Branding the 'Beur' Author : Minority Writing and the Media in France, 1983-2013 - Kleppinger, Kathryn A. (Contemporary French and francophone cultures., 2015)
This book reconsiders authorship by the descendants of North African immigrants to France by consulting how these authors' novels have been discussed and promoted in the national audio-visual media.